Comparative Analysis of Gut Microbiomes in Captive Tigers across Ex Situ Facilities in Peninsular Malaysia - Millawati, Gani; Mohd Ridwan, Abd Rahman; Mohd Kulaimi, N. A.; Khairulmunir, Mohamad; ABDUL-LATIFF, MUHAMMAD ABU BAKAR; Md Zain, Badrul Munir (Pleiades Publishing Ltd., 2024)
Tigers residing in captive environments are exposed to novel conditions that have been influenced by human activities, including altered environmental factors, modified diets, and more exposure to humans. This study aimed to identify the gut microbiome communities and diversity of captive tigers, with a primary focus on the Malayan tiger (Panthera tigris jacksoni), while considering various tiger subspecies housed across eight different ex situ facilities in Peninsular Malaysia. Most Malayan tigers are placed in captivity due to human-tiger conflicts and rescued cases. A total of 65 tiger fecal samples were extracted and then the extracted samples were pooled into 23 genomic DNAs based on locality, followed by age and sex. All samples were analyses by 16S rRNA gene amplicon sequencing targeting the V3−V4 hypervariable region. The result showed that captive tigers had the same gut microbiome composition but different relative abundances of the constituent phyla. Five dominant phyla identified across various ex situ facilities were Firmicutes, Actinobacteria, Proteobacteria, Fusobacteria, and Bacteroidota. The gut microbiome beta diversity was influenced by captivity environment and diet intake of captive tigers. This study also highlighted the presence of potentially pathogenic bacteria, which could significantly impact the health of tigers in captivity. This research provides fundamental information about the gut microbiome of Malayan tigers in captivity to develop the strategies for improving the management of Malayan tiger conservation.